2011
DOI: 10.1002/nag.1062
|View full text |Cite
|
Sign up to set email alerts
|

On the causes of pressure oscillations in low‐permeable and low‐compressible porous media

Abstract: SUMMARYNonphysical pressure oscillations are observed in finite element calculations of Biot's poroelastic equations in low-permeable media. These pressure oscillations may be understood as a failure of compatibility between the finite element spaces, rather than elastic locking. We present evidence to support this view by comparing and contrasting the pressure oscillations in low-permeable porous media with those in lowcompressible porous media. As a consequence, it is possible to use established families of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 28 publications
5
96
0
Order By: Relevance
“…Here the discrete flux and traction are defined in (17) and (20), utilizing that due to (18) and (21) we can (up to the sign) evaluate the expression for either K ∈ T σ . In order to show stability according to Definition 1 and verify Lemma 23, we combine the above errors to the stable error…”
Section: Convergence Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here the discrete flux and traction are defined in (17) and (20), utilizing that due to (18) and (21) we can (up to the sign) evaluate the expression for either K ∈ T σ . In order to show stability according to Definition 1 and verify Lemma 23, we combine the above errors to the stable error…”
Section: Convergence Resultsmentioning
confidence: 99%
“…In contrast, the solid subproblem does not lend itself trivially to mixed finite elements, and although much recent literature relates to this problem, simple low-order element combinations appear to be impossible to devise [6]. A thorough numerical investigation of various combinations of mixed methods for the full Biot equations has been reported [18]. An alternative to mixed finite elements (but similar in spirit) is to use staggered grids for the mechanics and flow equations [37,17].…”
Section: Definition 1 We Denote a Discretization Of Equations (1) Asmentioning
confidence: 99%
“…It is well-known that the standard finite element solution of the poroelasticity equations can present strong nonphysical oscillations in the fluid pressure, see for instance [1,7,8,15,29]. For example, this is the case when linear finite elements are used to approximate both displacement and pressure unknowns.…”
Section: Stable Discretization Of the Modelmentioning
confidence: 99%
“…We consider a porous material on which a low-permeable layer (K = 10 −8 ) is placed between two layers with unit permeability (K = 1), as shown in Fig. 4, see [15]. The boundary of the squared domain is split in two disjoint subsets 1 and 2 on which we assume the following boundary conditions: on the top, which is free to drain, a uniform load is applied, that is, whereas at the sides and bottom that are rigid the boundary is considered to be impermeable, that is,…”
Section: One-dimensional Problemmentioning
confidence: 99%
“…It has been suggested that this problem is caused by the saddle point structure in the coupled equations resulting in a violation of the famous LadyzhenskayaBabuska-Brezzi (LBB) condition, thus highlighting the need for a stable combination of mixed finite elements [23].…”
Section: Introductionmentioning
confidence: 99%